TREATY OF LISBON AND THE MAIN CHANGES AT THE COURT OF JUSTICE OF THE EUROPEAN UNION - Honorius CIRCA (Challenges of the Knowledge Society)
This paper analyzes the Court of Justice of the European Union after the Lisbon treaty and the changes that will be performed in order to increase the role of the Court in EU. We will discuss the Lisbon reform and the legacy of the European Constitution and the changes to the organization of the judiciary in the Union and to the appointment of its members. An important part of the paper will be dedicated to the procedure for future amendments of the Statute of the Court of Justice of the European Union and the creation of Specialized Courts. The conclusion of the paper will treat the future of the judicial structure of the Union and the challenges of the greater complexity of the decision-making process and of the binding nature of the Charter of Fundamental Rights. A new phase of judicial activism has begun in the European Court of Justice, a phase focused on the protection of fundamental rights. The European Charter of Fundamental Rights, as well as the Lisbon Treaty has strengthened the position of the Court of Justice.